Excessive alcohol consumption in the COVID-19 pandemic: a causality investigation (Research, Society and Development, 2022)
Along with the outbreak of COVID-19, prevention measures were introduced, especially those aimed at social distancing, in order to reduce the spread of the disease. However, due to such restriction measures and, in an already presumptuous way, the consumption of alcoholic beverages changed from the public to the household. This study aims to investigate the relationship between the COVID-19 pandemic and the consumption of alcoholic beverages by the population. From this perspective, such an investigation is justified by the growing increase in socio-emotional disorders in the context of social distancing, in order to minimize any emotional symptoms. It refers to an original, cross-sectional epidemiological study, carried out through an online questionnaire, with 162 participants. The relationship between alcohol consumption and sociodemographic variables was observed: gender, age group, schooling, monthly income and marital status; in addition to the variables: feeling alone, isolation affected and anxiety/depression. The present study identified that people who only know how to read and write, and people who feel alone had a significant association with increased alcohol consumption in the pandemic. Married people tended not to change their alcohol consumption during the pandemic. The sociodemographic variables, gender, age group, monthly income, and the variables isolation affected, and anxiety/depression showed no significant association with the change in alcohol consumption. In the final analysis, education, marital status and feeling alone were highlighted in association with increased alcohol consumption during the pandemic.